Program of activities physics- recreational in order to diminish the consumption of tobacco in the youth (Original) (Revista científica Olimpia, 2021)
The present article is about the elaboration of a program of activities physics- recreational in order to diminish the consumption of tobacco in the youth. The elaboration of the program has like objective favor the options for the occupation of the free time and the level of satisfaction of the youth. The activities introduced after applying the program they satisfy the recreational necessities of the youth, and  it  is notorious that they are of their I please, to their interests and motivations. This Program Influenced positively in the selected pattern, then many of the youth were reinserted the activities physical - recreational, some of them news and never before carried out for the settlers of the community, they incremented the recreational options and it  was achieved old level of satisfaction in the youth.
Keywords: physical – recreational activities, youth, consumption of tobacco